Environmentally Smart Nitrogen Performance in Northern Great Plains’ Spring Wheat Production Systems - Olga S. Walsh; Kefyalew Girma (International Journal of Agronomy)
Experiments were conducted in Montana to evaluate Environmentally Smart Nitrogen (ESN) as a nitrogen (N) source in wheat. Plots were arranged in a split-plot design with ESN, urea, and a 50%-50% urea-ESN blend at low, medium, and high at-seeding N rates in the subplot, with four replications. Measurements included grain yield (GY), protein (GP), and N uptake (GNU). A partial budget economic analysis was performed to assess the net benefits of the three sources. Average GY varied from 1816 to 5583 kg ha−1 and grain protein (GP) content ranged from 9.1 to 17.3% among site-years. Urea, ESN, and the blend resulted in higher GYs at 3, 2, and 2 site-years out of 8 evaluated site-years, respectively. Topdressing N improved GY for all sources. No trend in GP associated with N source was observed. With GP-adjusted revenue, farmer would not recover investment costs from ESN or blend compared with urea. With ESN costing consistently more than urea per unit of N, we recommend urea as N source for spring wheat in Northern Great Plains.